Adult psychosocial outcomes of children with specific language impairment, pragmatic language impairment and autism. - Whitehouse, A; Watt, H; Line, E; Bishop, D (2009)
BACKGROUND: The few studies that have tracked children with developmental language disorder to adulthood have found that these individuals experience considerable difficulties with psychosocial adjustment (for example, academic, vocational and social aptitude). Evidence that some children also develop autistic symptomatology over time has raised suggestions that developmental language disorder may be a high-functioning form of an autism spectrum disorder (ASD). It is not yet clear whether these outcomes vary between individuals with different subtypes of language impairment. AIMS: To compare the adult psychosocial outcomes of children with specific language impairment (SLI), pragmatic language impairment (PLI) and ASD. METHODS and PROCEDURES: All participants took part in research as children. In total, there were 19 young adults with a childhood history of Specific Language Impairment (M age = 24;8), seven with PLI (M age = 22;3), 11 with high functioning ASD (M age = 21;9) and 12 adults with no history of developmental disorder (Typical; n = 12; M age = 21;6). At follow-up, participants and their parents were interviewed to elicit information about psychosocial outcomes. OUTCOMES and RESULTS: Participants in the SLI group were most likely to pursue vocational training and work in jobs not requiring a high level of language/literacy ability. The PLI group tended to obtain higher levels of education and work in 'skilled' professions. The ASD participants had lower levels of independence and more difficulty obtaining employment than the PLI and SLI participants. All groups had problems establishing social relationships, but these difficulties were most prominent in the PLI and ASD groups. A small number of participants in each group were found to experience affective disturbances. The PLI and SLI groups showed lower levels of autistic symptomatology than the ASD group. CONCLUSIONS and IMPLICATIONS: The between-group differences in autistic symptomatology provide further evidence that SLI, PLI, and ASD are related disorders that vary along qualitative dimensions of language structure, language use and circumscribed interests. Childhood diagnosis showed some relation to adult psychosocial outcome. However, within-group variation highlights the importance of evaluating children on a case-by-case basis.